Common Whites : Class and Culture in Antebellum North Carolina - Cecil-Fronsman, Bill (Book collections on Project MUSE., 1992)
Class and culture in Antebellum North Carolina have been largely forgotten. In the past few years, several important studies have examined common whites in individual counties or groups of counties, but they have focused on family life, the economy, or other specific features of the common-white life. C ommon Whites: Class and Culture in Antebellum North Carolina is the first comprehensive examination of these nonslaveholders and small slaveholders in over forty years. Using North Carolina as a case in point, Bill Cecil-Fronsman has sketched a broad portrait of the world made by this group. Dra.